THE CONTRASTIVE OF COMMUNICATIVE CULTURE BETWEEN MAKASSARESE AND ENGLISH WITH SPECIAL REFERENCE TO INTRODUCTION - abbas, abbas (Universitas Hasanuddin, 2016)
This paper discusses the contrastive of communicative culture between Makassar people and Englishmen, specially in self-introduction. The contrastive culture aims at comparing the diffrence aspects of introducing between Makassar and English.This research uses the method of field research and library study. Field research is done to obtain manners both society in inroducing. Library study is meant to explore values and norms both society with special reference to introduction. Then those information, the writer does contrastive analysis till finding conclusion.Based on the whole information and the analysis results, the writer finds There are seven issues different introduction between Makassarese and English community that conveys not only verbal communication but also nonverbal communication. They are gender, age, status, kinship relation, shaking hand, eyes contact, and forming name. The differences are usually caused by contrastive world-view. Makassarese community is feeling strongly its traditional habit or culture from generation to generation what it known as Eastern Culture while English community is expanding its communicative system on technology entering globalization what it called as Western Culture.Keywords: contrastive culture, introduction, Makassar, English